1987
DOI: 10.1126/science.3029875
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Is a Component of Paired Helical Filaments in Alzheimer's Disease

Abstract: Paired helical filaments (PHF), which constitute a distinct type of pathological neuronal fiber, are the principal constituent of neurofibrillary tangles that occur in the brain of patients with Alzheimer's disease. Their insolubility in sodium dodecyl sulfate and urea has prevented the analysis of their subunit composition by gel electrophoresis. A monoclonal antibody (DF2) was isolated that specifically labeled PHF at both the light and electron microscopic levels. It labeled a small polypeptide (5 kilodalto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
314
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 803 publications
(333 citation statements)
references
References 22 publications
7
314
0
1
Order By: Relevance
“…116 In AD brain, the paired helical filaments (PHF) in tangles are ubiquitinated. 117,118 The level of ubiquitin in AD cerebral cortex is increased several-fold and correlates with the amount of neurofibrillary changes. 119 Using an ELISA method based on the monoclonal antibody 5-25, raised against PHF from AD brains, 120 Mehta and co-workers reported in 1985 high levels of "paired helical filaments antigen" in CSF in AD.…”
Section: Ubiquitinmentioning
confidence: 99%
“…116 In AD brain, the paired helical filaments (PHF) in tangles are ubiquitinated. 117,118 The level of ubiquitin in AD cerebral cortex is increased several-fold and correlates with the amount of neurofibrillary changes. 119 Using an ELISA method based on the monoclonal antibody 5-25, raised against PHF from AD brains, 120 Mehta and co-workers reported in 1985 high levels of "paired helical filaments antigen" in CSF in AD.…”
Section: Ubiquitinmentioning
confidence: 99%
“…Although ubiquitin was used as a marker for brain pathology, such as neurofibrillary tangles in Alzheimer's disease and Lewy bodies in Parkinson's disease (Mori et al 1987;Lowe et al 1988), no physiological or pathological role for ubiquitin in the nervous system was found until about a decade and a half ago. The first discovery of ubiquitin-proteasome-mediated degradation of a substrate relevant to synaptic plasticity in the nervous system was that of R subunits of PKA (Hegde et al 1993).…”
Section: The Upp and Long-term Synaptic Plasticitymentioning
confidence: 99%
“…Among these proteins, ubiquitin has been known to be the most constantly and robustly immunopositive in LBs, glial cytoplasmic inclusions, and other related lesions together with ␣-synuclein. The presence of ubiquitin in intracellular inclusions in synucleinopathies suggests that abnormally aggregated or misfolded proteins are targeted for ubiquitination in these inclusions in a similar fashion to tau in neurofibrillary tangles of Alzheimer's disease (24,25). Recently, Shimura et al (19) reported that glycosylated ␣-synuclein (␣Sp22) can be readily multiubiquitinated by parkin that functions as E3 ubiquitin ligase in vitro.…”
mentioning
confidence: 99%